Теоретичні основи механізму захисту прав людини в системі публічного управління - Бондарчук, Наталія Володимирівна; Bondarchuk, Nataliia; Францен, Ю. І.; Francen, Yu. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
Метою даного дослідження є аналіз теоретичних основ, сутності та механізму захисту прав людини в системі публічного управління України в сучасних умовах. Констатовано, що механізм захисту прав людини є фундаментальною складовою демократичного розвитку України. Його ефективна реалізація сприятиме зміцненню соціальної стабільності, посиленню довіри громадян до державних інституцій та забезпеченню відповідності сучасним глобальним викликам.Визначено, що ключовими компонентами механізмузахисту прав людиниє правові норми, принципи верховенства права, відповідні інституції (суди, органи публічного управління, інститут омбудсмена тощо), а також процедури, які забезпечують захист прав громадян. Наголошено на необхідності створення ефективної взаємодії між державними інституціями, громадянським суспільством та міжнародними організаціями.Викладено основні принципи функціонування механізмузахисту прав людини, серед яких принципи справедливості, рівності, верховенства права, добросовісності, гуманізму, свободи та прозорості. Ці принципи не лише створюють правову базу для діяльності державних органів, але й сприяють підвищенню довіри громадян до публічного управління.The aim of this study is to analyze the theoretical foundations, essence and mechanism of human rights protection in the public administration system of Ukraine in modern conditions.It is stated that the mechanism of human rights protection is a fundamental component of the democratic development of Ukraine.Its effective implementation will contribute to strengthening social stability, strengthening citizens' trust in state institutions and ensuring compliance with modern global challenges. It is proposedto consider the mechanism of ensuring human rights as a social mechanism, since it includes not only legal, but also organizational, institutional and social elements aimed at the harmonious functioning of society and ensuring compliance with the fundamental rights and freedoms of every citizen. Themechanism of human rights protection in the public administration system can be considered as a complex system that encompasses various legal, organizational and procedural means aimed at ensuring the implementation, protection and restoration of human rights.Its feature is the active role of state authorities and local self-government bodies, which through their functions guarantee the observance of the rights and freedoms of citizens It is determined that the key components of the human rights protection mechanism are legal norms, principles of the rule of law, institutions (courts, public administration bodies, the ombudsman institution, etc.), as well as procedures that ensure the protection of citizens' rights.The need to create effective interaction between state institutions, civil society and international organizations is emphasized. The main principles of the functioning of the mechanism are outlined, including the principles of justice, equality, rule of law, good faith, humanism, freedom and transparency.These principles not only create a legal basis for the activities of state bodies, but also contribute to increasing citizens' trust in public administration. The article emphasizes the need to develop new approaches to ensuring digital rights, such as the right to free access to information, the right to protection of personal data, digital identity, etc. It is stated that the protection of these rights is an important aspect of Ukraine's integration intothe European legal space.
Theoretical basis of the mechanism for protection of human rights in the public administration system
Keywords: захист прав людини; protection of human rights; механізм; mechanism; публічне управління; public administration; соціальний механізм; social mechanism; верховенство права; rule of law